Rising house prices in an open labour market - David Duffy; John D. FitzGerald; Ida Kearney (The Economic and Social Research Institute (ESRI), 2005)
In this paper we explore the consequences of the recent steep rise in house prices for the openness of the Irish labour market. Specifically we look at the possible effect rising house prices may have on the migration decision. Since many immigrants are in the household formation age group, and tend to be highly skilled, we argue that the boom in house prices, by reducing the attractiveness of Ireland for potential immigrants, could reduce labour supply. Thus housing emerges as an important infrastructural constraint affecting the labour market. To formulate the role of house prices in the migration decision we use a structural model of the determination of output, labour supply and labour demand in Ireland. We modify the basic model in a number of ways: firstly we endogenise the determination of house prices using structural equations for the demand and supply of housing; secondly we separate out the user cost of housing in the migrant's cost of living index; and thirdly we endogenise the determination of consumer prices. Simulation results suggest that rising house prices, by discouraging potential migrants, could significantly reduce the growth potential of the economy, shifting the balance of labour market growth from employment to wages, with a consequent deterioration in competitiveness. The welfare effects of this differ for different groups; there are unambiguous gains for current home owners while immigrants, first time buyers and those with lower labour market skills are net losers.
Keywords: 330; housing; labour market; migration; Immobilienpreis; Ausländische Arbeitskräfte; Arbeitsangebot; Irland